FRI0425 LITERATURE REVIEW OF PATIENT PERSPECTIVES ON THE MANAGEMENT AND TREATMENT OF PSORIATIC ARTHRITIS. (June 2019) - Boonen, Annelies; Betteridge, Neil; Pinter, Andreas; Hill, Julie; Anand, Savita; Mchorney, Colleen; Reed, Catherine
Abstract : Background: A patient-centred approach to the management and drug treatment of psoriatic arthritis (PsA) has been advocated by a multidisciplinary group of experts to improve skin and joint symptoms and health-related quality of life (HRQoL). 1 Objectives: To examine perspectives of patients with PsA on: (1) disease management and treatment goals, (2) disease management and treatment satisfaction, and (3) treatment adherence, including reasons for discontinuation. Areas of interest were those related to medication, symptom resolution, everyday living and overall HRQoL. Methods: A targeted literature review was conducted to identify peer-reviewed literature on patient experience with PsA management and drug-treatment. English-language articles published between 1 January 2010–8 October 2018 reporting qualitative or quantitative evidence from cross-sectional or longitudinal observational studies were identified from searches conducted using MEDLINE (via PubMed) and Embase. Selection criteria included adult patients with PsA (self-reported or clinician-diagnosed); drug-treatment studies could consider only regulatory-approved treatments for PsA and other studies had to provide evidence of patient perspectives on disease management and treatment goals, experiences and/or satisfaction. Studies involving paediatric/adolescent populations were excluded, as were results for PsA were not distinguishable from other diseases. Results: The literature search identified 266 titles, of which 48 duplicates were removed. The remaining 218 abstracts were screened: 58 full-text articles were assessed for eligibility and 16 articles were selected for full-text review. Of these 16 articles, 9 were primarily related to patient perspective on disease management, 6 to patient satisfaction and 1 to treatment adherence; some articles covered more than one of these objectives. None of the articles studied whether explicit consideration of treatment goals from the patient perspective would influence management or outcome of care. Symptom resolution, reduced fatigue, improved sexual relations, improved HRQoL and ability to participate in daily activities were consistently identified by patients as important aspects for disease management and daily living with PsA. Articles on patient satisfaction focused largely on general satisfaction with medication rather than satisfaction specifically with holistic PsA management. Notwithstanding, symptom resolution was clearly linked to greater patient satisfaction with medication. Patient dissatisfaction with PsA treatment was influenced by their attitude towards treatment, concerns about PsA medication, the physician-patient relationship and lack of patient involvement in decision-making. Treatment adherence has not been widely explored but mainly relates to perceptions about, and experiences with, medications, including efficacy and adverse events. Conclusion: This literature review identified a lack of research on patient perspectives of PsA management and treatment goals. It also highlighted the lack of patient involvement in determining management and/or setting personal goals, which may ultimately affect satisfaction. There remains a lack of clarity on PsA symptoms and other disease- or patient-related parameters that impact patient satisfaction/dissatisfaction and patient-centred reasons for treatment discontinuation. The findings of this review will be used to develop a PsA patient survey to further explore patient perspectives to improve care in PsA. References: [1] Betteridge N, et al. J Eur Acad Dermatol Venereol 2016; 30: 576–85. Disclosure of Interests: Annelies Boonen: None declared, Neil Betteridge Consultant for: Amgen, Eli Lilly, Grunenthal, GSK, Heart Valve Voice, Janssen, Roche, Sanofi Genzyme and Sanofi Regeneron, Speakers bureau: Amgen, Eli Lilly, Grunenthal, GSK, Heart Valve Voice, Janssen, Roche, Sanofi Genzyme and Sanofi Regeneron, Andreas Pinter Consultant for: AbbVie, Almirall Hermal, Amgen, Biogen Idec, Boehringer Ingelheim, Celgene, GSK, Eli Lilly and Company, Galderma, Hexal, Janssen, LEO Pharma, Medac, Merck Serono, Mitsubishi, MSD, Novartis, Pfizer, Tigercat Pharma, Regeneron, Roche, Sandoz Biopharmaceuticals, Schering-Plough and UCB Pharma, Speakers bureau: AbbVie, Almirall Hermal, Amgen, Biogen Idec, Boehringer Ingelheim, Celgene, GSK, Eli Lilly and Company, Galderma, Hexal, Janssen, LEO Pharma, Medac, Merck Serono, Mitsubishi, MSD, Novartis, Pfizer, Tigercat Pharma, Regeneron, Roche, Sandoz Biopharmaceuticals, Schering-Plough and UCB Pharma, Julie Hill Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Savita Anand Consultant for: Contracted by Eli Lilly and Company to conduct the literature review., Colleen McHorney Consultant for: Contracted by Eli Lilly and Company to conduct the literature review., Catherine Reed Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company